2013
DOI: 10.2521/jswtb.49.65
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Long-Term Variation of Phytoplankton Biovolume and Gelatinous Sheath Volume in Lake Biwa

Abstract: Chemical oxygen demand (COD) in Lake Biwa has not been improved during the past quarter century in spite of decreases in organic loadings from watershed and total phytoplankton biovolume. In addition, an increase in cyanobacteria has been observed in Lake Biwa. Most of cyanobacteria have a large volume of gelatinous sheath, which is usually called extracellular polysaccharides (EPS) and may play a significant role in COD in the lake. Therefore, we analyzed long-term variation of phytoplankton biovolume and EPS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Regarding the long-term trend of the total biovolume of phytoplankton cells in the northern basin of Lake Biwa (0.5 m), research showed that the average total biovolume ranged from 1.5 to 1.8 mm 3 L −1 from 2000 to 2009, corresponding to 63% to 85% of the levels observed from 1980 to 1989 [ 33 ]. Although the total biovolume decreases, the total volume of mucilage sheaths surrounding the phytoplankton cells (16 to 21 mm 3 L −1 during 2000 and 2009) reaches more than twice the levels of 1980–1989 and 1990–1999, suggesting an increase in phytoplankton species with increasing sheath content.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the long-term trend of the total biovolume of phytoplankton cells in the northern basin of Lake Biwa (0.5 m), research showed that the average total biovolume ranged from 1.5 to 1.8 mm 3 L −1 from 2000 to 2009, corresponding to 63% to 85% of the levels observed from 1980 to 1989 [ 33 ]. Although the total biovolume decreases, the total volume of mucilage sheaths surrounding the phytoplankton cells (16 to 21 mm 3 L −1 during 2000 and 2009) reaches more than twice the levels of 1980–1989 and 1990–1999, suggesting an increase in phytoplankton species with increasing sheath content.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 18-year data of the abundance of fi tous Mn particles observed at a depth of 90 m and the biovolume of phytoplankto m were used. The total biovolume was expressed as the sum of the biovolumes of ophyceae (cyanobacteria), Chlorophyceae (including Charophyceae; green algae) lariophyceae (diatoms), Chrysophyceae, Dinophyceae, and Cryptophyceae, whic calculated from the cellular or colony sizes, as described elsewhere (Kishimoto et al The biovolume data obtained from 2002 to 2009 at the Imazuoki-chuo point wer lished previously [32,33].…”
Section: Study Site and Available Water Quality Datamentioning
confidence: 99%
“…Regarding the long-term trend of the total biovolume of phytoplankton cells in the northern basin of Lake Biwa (0.5 m), research showed that the average total biovolume ranged from 1.5 to 1.8 mm 3 L -1 from 2000-2009, corresponding to 63% to 85% of the levels observed from 1980-1989 [33]. Although the total biovolume decreases, the total volume of EPS surrounding the phytoplankton cells (16 to 21 mm 3 L -1 during 2000 and 2009) reaches more than twice the levels of 1980-1989 and 1990-1999, suggesting the increase in phytoplankton species with increasing EPS content.…”
Section: Discussionmentioning
confidence: 99%
“…The total biovolume was expressed as the sum of the biovolumes of Cyanophyceae (cyanobacteria), Chlorophyceae (including Charophyceae; green algae), Bacillariophyceae (diatoms), Chrysophyceae, Dinophyceae, and Cryptophyceae, which were calculated from the cellular or colony sizes, as described elsewhere (Kishimoto et al 2013). The biovolume data obtained from 2002 to 2009 at the Imazuoki-chuo point were published previously [32,33].…”
Section: Study Site and Available Water Quality Datamentioning
confidence: 99%
“…It has been reported that the increase in refractory DOM may be attributed to the contribution of not only humic substances from soils around the rivers flowing into Lake Biwa but also algal DOM from phytoplankton in the lake. 3,[8][9][10][11][12][13][14] Furthermore, it has been clarified that humic substances might be released regularly from lake sediment. 15,16 However, few studies of the characteristics and contribution of algal DOM to refractory DOM in lake water have been done.…”
Section: Introductionmentioning
confidence: 99%